Factorise : 8x 3 - ( 2x - y ) 3 .
Answers
Answered by
144
Given, 8x^3 - (2x - y) ^3
= (2x) ^3 - (2x - y) ^3
Using the formula:
a^3 - b^3= (a - b)(a^2 + ab + b^2) -------- eq.(1)
Putting the value of a = 2x, b = (2x – y) in the above formula; we get
= (2x – (2x+y)) {(2x) ^2 - 2x*(2x - y) + (2x - y) ^2}
= y {(4x^2 - 4x^2 + 2xy + 4x^2 - 4xy + y^2)}
= y (4x^2 - 2xy + y^2)
Therefore, factorized form of the given problem is y (4x^2 - 2xy + y^2).
Answered by
31
putting
a^3-b^3=x^3-3x^2y+3xy^2-y^3
8x3-3 (8x2)(2x-y)+3 (8x)(2x-y)2-(2x-y)3
that set now solve it
Similar questions